Understanding eHealth Cognitive Behavioral Therapy Targeting Substance Use: Realist Review - Shams, Farhud; Wong, James S H; Nikoo, Mohammadali; Outadi, Ava; Moazen-Zadeh, Ehsan; Kamel, Mostafa M; Song, Michael Jae; Jang, Kerry L; Krausz, Reinhard Michael (JMIR Publications, 2021)
BackgroundThere is a growing body of evidence regarding eHealth interventions that target substance use disorders. Development and funding decisions in this area have been challenging, due to a lack of understanding of what parts of an intervention work in which context. ObjectiveWe conducted a realist review of the literature on electronic cognitive behavioral therapy (eCBT) programs for substance use with the goal of answering the following realist question: "How do different eCBT interventions for substance use interact with different contexts to produce certain outcomes?" MethodsA literature search of published and gray literature on eHealth programs targeting substance use was conducted. After data extraction, in order to conduct a feasible realist review in a timely manner, the scope had to be refined further and, ultimately, only included literature focusing on eCBT programs targeting substance use. We synthesized the available evidence from the literature into Context-Mechanism-Outcome configurations (CMOcs) in order to better understand when and how programs work. ResultsA total of 54 papers reporting on 24 programs were reviewed. Our final results identified eight CMOcs from five unique programs that met criteria for relevance and rigor. ConclusionsFive strategies that may be applied to future eCBT programs for substance use are discussed; these strategies may contribute to a better understanding of mechanisms and, ultimately, may help design more effective solutions in the future. Future research on eCBT programs should try to understand the mechanisms of program strategies and how they lead to outcomes in different contexts.